Lithium Monitoring in Adult Community Mental Health Patients: Evaluating Current Practices in Al Ain, United Arab Emirates - Mouza AlDhaheri; Salma AlAzeezi; Fatima AlShanqiti; Taibah AlMadhaani; Syed Fahad Javaid (BJPsych Open)
Aims: Lithium is a well-established mood stabiliser used for conditions such as bipolar disorder, mania, and depression. Given its narrow therapeutic index, regular monitoring is essential to prevent toxicity, which can cause confusion, seizures, coma, or death. This audit evaluated long-term lithium monitoring compliance for adult community-based patients at the Behavioural Science Institute, Al Ain Hospital, United Arab Emirates. We assessed adherence to local hospital guidelines, which align with The National Institute for Health and Clinical Excellence (NICE) Guideline CG185, recommending six-monthly checks of serum lithium levels, thyroid function, renal function, calcium levels, and BMI, with some patient groups requiring more frequent testing notably older adults, those taking medications interacting with lithium, and patients at risk of kidney, thyroid, or electrolyte abnormalities.